Konsep Pendidikan Anak dalam Islam Menurut Syekh Ali Jaber dan Buya Hamka - Eva Sasmita; Deswalantri; Iswantir M; Januar Januar (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
This research is motivated by the phenomenon of the decline of character and Islamic values in children during the digital era. Given the importance of the parent's role as the primary educator, references from relevant ulema are needed to strengthen the foundation of religious education from an early age. This study aims to determine and analyze the concept of child education in Islam in terms of Akidah (faith), Ibadah (worship), and Akhlak (morals) according to the perspectives of Sheikh Ali Jaber and Buya Hamka. This research is a type of library research. Primary data sources in this study include books and the thoughts of Sheikh Ali Jaber and Buya Hamka. Data collection techniques were carried out through documentation, while data analysis used the content analysis method. The results of the study show that: (1) The concept of child education in Islam according to Sheikh Ali Jaber includes the aspect of Akidah (teaching monotheism, faith, daily prayers, and love for the Prophet), the aspect of Ibadah (teaching prayer, memorizing the Qur'an, discipline in worship, and almsgiving), and the aspect of Akhlak which emphasizes using positive words and avoiding negative words that can break a child's heart. (2) The concept of children's education in Islam according to Buya Hamka, includes Aqidah education, namely educating children with monotheism, educating children with faith, educating children with piety. Worship Education, namely educating children to pray, educating children to read the Qur'an, educating children to be disciplined and regular in worship. Moral Education, namely educating children to be polite, educating children to respect each other, educating children to maintain social interactions, giving children Islamic names, educating not to spoil children, educating not to use force, educating children to be independent, educating children to be confident, educating children to strive, educating children to take care of their eyes and jewelry, educating children to respect their parents, educating children not to be rude, educating children to think kindly, educating children to help each other, educating children to be brave, educating children to be honest.